2014
DOI: 10.1159/000367999
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for Hepatocellular Carcinoma Measuring 2 cm or Smaller: Results and Risk Factors for Local Recurrence

Abstract: Objective: The purpose of this study was to evaluate the risk factors for local recurrence with radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) measuring ≤2 cm. Methods: This study involved 234 patients with 274 HCCs measuring ≤2 cm who had undergone RFA as the initial treatment. The mean tumor diameter was 1.478 cm. The median follow-up period was 829 days. We evaluated the post-RFA cumulative local recurrence rate and analyzed the risk factors contributing to clinical outcomes. Results: Cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…This finding suggests that RFA can be used to achieve a high local control rate when ablation is judged to be possible, even if the tumors are located adjacent to vessels. In previous literature, many risk factors of local recurrence have been reported including location (adjacent to a major vessel/bile duct, (21) on the liver surface, (22,23) subcapsular (23) ), irregular gross type, (22) small ablative margin, (21,22) and large tumor size. (24) In clinical practice, tumors with such risk factors may be judged as For all patients' analysis, the rates of liver toxicities defined as Child-Pugh score deterioration ≥2 in acute and late phases following RFA and SBRT-HFRT were similar.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that RFA can be used to achieve a high local control rate when ablation is judged to be possible, even if the tumors are located adjacent to vessels. In previous literature, many risk factors of local recurrence have been reported including location (adjacent to a major vessel/bile duct, (21) on the liver surface, (22,23) subcapsular (23) ), irregular gross type, (22) small ablative margin, (21,22) and large tumor size. (24) In clinical practice, tumors with such risk factors may be judged as For all patients' analysis, the rates of liver toxicities defined as Child-Pugh score deterioration ≥2 in acute and late phases following RFA and SBRT-HFRT were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Local tumor progression after RFA was investigated in many studies, and the rate of progression differed in all studies [2][3][4][5]20]. Siina et al [3].…”
Section: Discussionmentioning
confidence: 99%
“…showed that 5-and 10-year local tumor progression rates were both 3.2%, and the serum DCP level alone was significantly related to local tumor progression. Kono et al [20]. reported the outcome of RFA in patients with 2-cm or smaller HCC.…”
Section: Discussionmentioning
confidence: 99%
“… proposed a new gross classification (single nodular type, single nodular type with extranodular growth, confluent multinodular type and infiltrative type), which was accepted by the Liver Cancer Study Group of Japan and has been widely used. A recent study reported that even for HCC of 2 cm or less, the gross type was significantly associated with local recurrence after RFA . However, the survival significance of gross classification in single small HCC treated with RFA has not been previously reported.…”
Section: Introductionmentioning
confidence: 96%